Interactions between FGF18 and retinoic acid regulate differentiation of chick embryo limb myoblasts - Mok, Gi Fay; Cardenas, Ryan; Anderton, Helen; Campbell, Keith H.S.; Sweetman, Dylan (Elsevier, 2014)
During limb development Pax3 positive myoblasts delaminate from the hypaxial dermomyotome of limb level somites and migrate into the limb bud where they form the dorsal and ventral muscle masses. Only then do they begin to differentiate and express markers of myogenic commitment and determination such as Myf5 and MyoD. However the signals regulating this process remain poorly characterised. We show that FGF18, which is expressed in the distal mesenchyme of the limb bud, induces premature expression of both Myf5 and MyoD and that blocking FGF signalling also inhibits endogenous MyoD expression. This expression is mediated by ERK MAP kinase but not PI3K signalling. We also show that retinoic acid (RA) can inhibit the myogenic activity of FGF18 and that blocking RA signalling allows premature induction of MyoD by FGF18 at HH19. We propose a model where interactions between FGF18 in the distal limb and retinoic acid in the proximal limb regulate the timing of myogenic gene expression during limb bud development.